2002
DOI: 10.1128/jvi.76.3.1077-1088.2002
|View full text |Cite
|
Sign up to set email alerts
|

The Cyclin-Dependent Kinase Inhibitor Roscovitine Inhibits the Transactivating Activity and Alters the Posttranslational Modification of Herpes Simplex Virus Type 1 ICP0

Abstract: The cyclin-dependent kinase (cdk) inhibitor Roscovitine (Rosco) reduces transcription of herpes simplex virus early genes significantly, even in the presence of wild-type levels of immediate-early (IE) viral proteins, suggesting that the transactivating functions of IE proteins may require the activities of one or more Roscosensitive cdk (L. M. Schang, A. Rosenberg, and P. A. Schaffer, J. Virol. 73:2161-2172, 1999). Based on this observation, we sought to determine whether Rosco alters the transactivating acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
53
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 90 publications
3
53
0
Order By: Relevance
“…While it has long been established that ICP0 undergoes phosphorylation during infection (2,3,15,52), little is known as to how these phosphorylation events specifically regulate the biological functions of ICP0 (3,4,16,17,43). In this study we initially sought to determine whether ICP0 phosphorylation modulated its E3 ubiquitin ligase activity and its associated ability to induce the dispersal and degradation of PML and Sp100 from ND10.…”
Section: Discussionmentioning
confidence: 99%
“…While it has long been established that ICP0 undergoes phosphorylation during infection (2,3,15,52), little is known as to how these phosphorylation events specifically regulate the biological functions of ICP0 (3,4,16,17,43). In this study we initially sought to determine whether ICP0 phosphorylation modulated its E3 ubiquitin ligase activity and its associated ability to induce the dispersal and degradation of PML and Sp100 from ND10.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that the phosphorylation state of ICP0 is altered during the course of the viral replication cycle (1,2,15,53,68), suggesting that differential phosphorylation of ICP0 might activate or inhibit one or more specific functions of this key viral regulatory protein. Consequently, the identity of specific phosphorylation sites in regions I and II of ICP0, the potential kinases that phosphorylate these sites, and their temporal regulation and roles in ICP0's functions will likely elucidate new mechanisms in the switch between the lytic and latent infections of HSV-1.…”
Section: Discussionmentioning
confidence: 99%
“…Cellular cyclin-dependent kinases (cdks) and the viral kinase UL13 have been reported to phosphorylate ICP0 or to be required for maximal levels of ICP0 phosphorylation in the infected cells (3,15,53). The activities of cdks appear to modulate the biological properties of ICP0, including its transactivating activity (15,17). To directly determine the role phosphorylation plays in ICP0 functions, we mapped three phosphorylated regions in ICP0 and mutated phospho-acceptor sites in each of these regions, creating the mutants Phos 1, 2, and 3 (16).…”
mentioning
confidence: 99%
“…Rosco also inhibits chromatin remodeling on the adenovirus type 12 E2 promoter by the viral transcription factor E1A 12S (23). Rosco inhibits posttranslational modifications of two HSV-1 IE transcriptional regulators, ICP0 and ICP4 (1,18) and the transcription-regulatory activity of ICP0 (18,19). However, it also inhibits the accumulation of IE, E, and L HSV-1 transcripts in less than 2 h and even in the presence of cycloheximide (CHX) (73)(74)(75).…”
mentioning
confidence: 99%
“…However, there are no DNA sequences unique to the promoters of all E genes, and many non-HSV-1 promoters recombined into the viral genome are regulated as HSV-1 E promoters (i.e., they require IE proteins) (78,79). Consequently, it is currently accepted that ICP0 and ICP4 activate transcription through indirect mechanisms that operate independently of promoter-specific sequences or transcription factors, which are the subject of intensive research (1,7,18,19,21,22,34,54,60,80). ICP4 also inhibits the expression of IE genes, by binding with high affinity to sequences near their transcription start sites (35).…”
mentioning
confidence: 99%